The Effect of Reasurposing Learning Model on Food Literacy Skills and Caring Atitude Toward Food Consumption - mochammad ali mashur; Emi Farida Anjasmorowati; Fathimah Fathimah (Universitas Darussalam Gontor, 2023)
Background: The behavior of students who tend to ignore the consumption of unhealthy foods and lack of understanding of the negative impact of additives on food will increase the risk of decreasing the level of health in students. Objective : Determine the effect of the Reasurposing learning model on food literacy skills and caring attitudes towards food consumption on digestive system material. Methods : This research design is a pseudo experiment. The research sample was XI MIPA class students totaling 30 in the 2020/2021 academic year at SMA Darul Ulum 2 Unggulan BPPT and using purposive sampling technique. The study used one experimental group treated with the reasurposing learning model. The dependent variables of this study are food literacy and caring attitude towards food consumption. The independent variables are reasurposing learning model. Data on food literacy skills were obtained through the administration of pretests and post-tests, while data on attitudes towards food consumption were obtained through filling out questionnaires given at the initial and the final learning meeting. Food literacy skills were analyzed using the Paired sample t-test and data on caring attitudes towards food consumption were analyzed using the Gain score and interpreted based on the parameters. The research was conducted from August-October 2020 online using the Google classroom online platform and whatapp application. Results : The application of the Reasurposing learning model had an effect of 20.67% (p value = 0.000) in improving students' food literacy, and the attitude of caring for food consumption increased with an N-gain value of 76.40%. Conclusion: application of reasurposing model has an effect on food literacy and caring attitudes in food consumption. Key words : Reasurposing, food literacy, caring attitude towards food consumption